Do Consumers Perceive Impulsive Buying and Pain of Payment? E-Commerce Transactions Using Pay Later, E-Wallet, and Cash-On-Delivery - Bakar, Resekiani Mas; Fauziyah, Nurul; Rahmat, Abdul (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
This study investigates how modern payment options, pay-later, e-wallets, and COD affect online shopping behavior, specifically on impulsive purchases and the feeling of regret after spending, known as the pain of payment. While numerous studies have individually assessed the impact of these payment modalities, there was a paucity of research examining the combined effect of these three contemporary payment methods within experimental frameworks. This study also examines whether buying groceries or fashion items influences these behaviors. The research involved 162 consumers divided into 6 groups based on the type of payment method (pay-later, e-wallet, cash-on-delivery) and type of products (grocery and fashion). The study found that the chosen payment method has no significant impact on impulsive buying behavior. However, customers are more likely to purchase fashion items impulsively than groceries. The pay-later option, especially for fashion items, led to the most impulsive buying and the strongest feeling of payment regret. On the other hand, using COD for fashion items was the least popular, and e-wallets generally led to lower overall spending. The study also found that people spend more time shopping for groceries than fashion. Both thought processes and emotions influenced the decision to buy. Interestingly, paying with COD helped improve self-control and reduce negative feelings. Based on the control theory of self-regulation, this research provides insights into managing spending and achieving customer financial goals, highlighting the connection between payment options, impulsive buying, and consumer well-being.